Transcranial Direct Current Stimulation to Enhance Training Effectiveness in Chronic Post-Stroke Aphasia: A Randomized Controlled Trial Protocol - Stahl, Benjamin; Darkow, Robert; von Podewils, Viola; Meinzer, Marcus; Grittner, Ulrike; Reinhold, Thomas; Grewe, Tanja; Breitenstein, Caterina; Flöel, Agnes (Frontiers in Neurology, 2019)
Background. Intensive speech-language therapy (SLT) can promote recovery from chronic post-stroke aphasia, a major consequence of stroke. However, effect sizes of intensive SLT are moderate, potentially reflecting a physiological limit of training-induced progress. Transcranial direct current stimulation (tDCS) is an easy-to-use, well-tolerated and low-cost approach that may enhance effectiveness of intensive SLT. In a recent phase-II randomized controlled trial, 26 individuals with chronic post-stroke aphasia received intensive SLT combined with anodal-tDCS of the left primary motor cortex (M1), resulting in improved naming and proxy-rated communication ability, with medium-to-large effect sizes. Aims. The present work seeks to establish the incremental benefit from anodal-tDCS of M1 in a phase-III randomized controlled trial with adequate power, ecologically valid outcomes, and evidence-based SLT. Methods. The planned study is a prospective randomized placebo-controlled (using sham-tDCS), parallel-group, double-blind, multi-center, phase-III superiority trial. 130 individuals with aphasia at least six months post-stroke will be recruited in more than 18 in- and outpatient rehabilitation centers. Outcomes. The primary outcome focuses on communication ability in chronic post-stroke aphasia, as revealed by changes on the Amsterdam-Nijmegen Everyday Language Test (A-scale; primary endpoint: 6-month follow-up; secondary endpoints: immediately after treatment, and 12-month follow-up). Secondary outcomes include measures assessing linguistic-executive skills, attention, memory, emotional well-being, quality of life, health economic costs, and adverse events (endpoints: 6-month follow up, immediately after treatment, and 12-month follow-up). Discussion. Positive results will increase the quality of life for persons with aphasia and their families while reducing societal costs. After trial completion, a workshop with relevant stakeholders will ensure transfer into best-practice guidelines and successful integration within clinical routine.